2018
DOI: 10.1371/journal.ppat.1006974
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase inhibitors enhance the efficacy of frontline drugs against Mycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis (Mtb) remains a grave threat to world health with emerging drug resistant strains. One prominent feature of Mtb infection is the extensive reprogramming of host tissue at the site of infection. Here we report that inhibition of matrix metalloproteinase (MMP) activity by a panel of small molecule inhibitors enhances the in vivo potency of the frontline TB drugs isoniazid (INH) and rifampicin (RIF). Inhibition of MMP activity leads to an increase in pericyte-covered blood vessel number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 65 publications
4
54
0
Order By: Relevance
“…The clear correlation between MXF abundance and relative distance from the outer lesion border is in keeping with previous studies showing that functionally abnormal vasculature increases as the distance from granuloma border increases, leading to correspondingly impaired small molecule distribution ( Datta et al, 2015 ). In these studies, the authors showed that therapies thought to achieve vessel normalization, and thus improve vascular function, appear to improve small molecule delivery to TB lesions ( Datta et al, 2015 ) or potentiate TB therapy ( Xu et al, 2018 ). These observations are reminiscent of oncology drug penetration concepts, where excessive angiogenesis generates a disorganized and leaky blood vessel network leading to poor drug delivery to the tumor core ( Azzi et al, 2013 ; Di Paolo and Bocci, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The clear correlation between MXF abundance and relative distance from the outer lesion border is in keeping with previous studies showing that functionally abnormal vasculature increases as the distance from granuloma border increases, leading to correspondingly impaired small molecule distribution ( Datta et al, 2015 ). In these studies, the authors showed that therapies thought to achieve vessel normalization, and thus improve vascular function, appear to improve small molecule delivery to TB lesions ( Datta et al, 2015 ) or potentiate TB therapy ( Xu et al, 2018 ). These observations are reminiscent of oncology drug penetration concepts, where excessive angiogenesis generates a disorganized and leaky blood vessel network leading to poor drug delivery to the tumor core ( Azzi et al, 2013 ; Di Paolo and Bocci, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of MMPs by marimastat reduced both granuloma formation and bacterial load in Mtb infection, suggesting that MMP‐targeting intervention could be considered as a supportive therapy in TB treatment. Administration of marimastat alone did not show protective response in Mtb‐ infected C57BL/6J mice; however, when administered in combination with either rifampin or isoniazid as adjunctive treatment, it increased the drug exposure in infected lung tissues and caused a reduction in bacterial burden of lungs when compared with animals treated with rifampin or isoniazid alone . In contrast, administration of adjunctive cipemastat, an orally available potent inhibitor of MMP‐7, increased the frequency of cavitation, immunopathology and mortality in Mtb‐ infected C3HeB/FeJ .…”
Section: Inhibition Of Mmps: Unleashing Their Therapeutic Rolesmentioning
confidence: 97%
“…However, it is important to note that the substance shows a significant growth inhibitory effect on M. tuberculosis in broth (MIC 2.5 µg/mL) making it difficult to differentiate between selective host directed and antibacterial effects in these experiments. Experiments with more selective MMP inhibitors such as marimastat (BB-2516), a collagen peptidomimetic broad spectrum MMP inhibitor, showed adjuvant activity in M. tuberculosis-infected mice when combined with isoniazid or rifampicin [99]. In contrast to doxycycline, monotherapy with marimastat had no effect on lung bacterial burden [99].…”
Section: Targeting Matrix Metalloproteinases For Improved Tissue Repairmentioning
confidence: 99%
“…Experiments with more selective MMP inhibitors such as marimastat (BB-2516), a collagen peptidomimetic broad spectrum MMP inhibitor, showed adjuvant activity in M. tuberculosis-infected mice when combined with isoniazid or rifampicin [99]. In contrast to doxycycline, monotherapy with marimastat had no effect on lung bacterial burden [99]. 3.…”
Section: Targeting Matrix Metalloproteinases For Improved Tissue Repairmentioning
confidence: 99%